Commognitive Kesalahan Mahasiswa Melalui Aktivitas Diskusi dalam Menyelesaikan Soal Cerita - Agustin, Devi Rahayu; Rokhmawati, Ana (Pendidikan Matematika Universitas PGRI Yogyakarta, 2023)
Describing students’ cognitive errors in solving binomial problems using calculations and minitab. This type of research uses descriptive qualitative with the research subjects, which were 17 Mathematics Education Class 2020A students at one of the Private Universities (PTS) in Lumajang Regency. The results obtained are the ability of students with research instruments in the form of math ability test sheets, group assignment sheets, recording tools. The results of cognitive errors obtained from the high category in the form of word usage errors such as incomplete in writing known. Narrative errors such as not writing concepts in calculations. Visual mediator errors caused by low understanding of binomial concepts. Next, the errors made by the medium and low categories are the same. The errors are in the form of word usage errors such as errors in translating language in story problems and incomplete in writing known. Narrative errors such as not writing the concept of binomial in the calculation. Routine errors such as errors in calculations caused by incorrect previous steps and not writing conclusions. Keywords: Comognitive Error; Discussion Activity; Story Problem; Binomial